The Role of Feedback in Early Childhood Development: A Systematic Review of Cognitive, Social-Emotional, and Motivational Impacts - Lalu Mohammad Abid Zainul Puad (Lia Center of Research and Education, 2025)
Feedback represents a fundamental pedagogical mechanism with substantial impact on the holistic development of young children. This systematic review analyzes the role of feedback in shaping cognitive, social-emotional, and motivational developmental domains in children aged 0-8 years. Synthesis of 35 empirical studies demonstrates that high-quality feedback, characterized by specificity, timeliness, process orientation, and developmental appropriateness, yields significant improvements in metacognitive skills (d=0.52), emotional regulation (d=0.48), and intrinsic motivation (d=0.61). Analysis reveals that process feedback is superior to person feedback in developing growth mindset (β=0.43, p<0.001) and academic resilience. However, contextual factors such as child temperament characteristics, cultural norms, and teacher-student relationship quality moderate feedback effectiveness. Practical implications include the need for systematic professional development programs for educators, emphasizing culturally responsive, evidence-based feedback techniques. This research contributes theoretically by integrating perspectives from cognitive psychology, developmental theory, and early childhood pedagogy to construct a comprehensive model of feedback mechanisms in early learning.